The Influence Of Principal Leadership and Competence On The Performance Of State Elementary School Teachers In Muara Telang District - Dedi Priyanto; Nila Kesumawati; Yasir Arafat (International Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the influence of principal leadership and principal competence on the performance of public elementary school teachers in Muara Telang District, both partially and simultaneously. The research is motivated by the ongoing variation in teacher performance in the aspects of planning, implementation, and evaluation of learning, as well as the suboptimal implementation of academic supervision and teacher coaching by the principal. The study uses a quantitative approach with a survey method. The research population is all 114 public elementary school teachers in Muara Telang District, with a research sample of 89 teachers determined using the Slovin formula. Data collection is carried out through a Likert scale questionnaire that has been tested for validity and reliability. Data analysis techniques use simple linear regression and multiple linear regression with the help of the SPSS program version 26. The results of the study indicate that: (1) principal leadership influences teacher performance. (2) principal competence influences teacher performance. (3) principal leadership and principal competence influence teacher performance. These findings indicate that improving teacher performance requires synergy between effective principal leadership and adequate principal competence in managing schools and implementing continuous academic supervision.